Radar‐based monitoring of glass fiber reinforced composites during fatigue testing. Issue 10 (24th June 2021) - Moll, Jochen; Maetz, Thomas; Maelzer, Moritz; Krozer, Viktor; Mischke, Kevin; Krause, Stefan; Bagemiel, Oliver; Nuber, Andreas; Kremling, Stefan; Kurin, Thomas; Lurz, Fabian; Weigel, Robert; et al.
Summary: This work aims at radar sensors in the frequency band from 57 to 64 GHz that can be embedded in wind turbine blades during manufacturing, enabling non‐destructive quality inspection directly after production and structural health monitoring (SHM) during the complete service life of the blade. In this paper, we show the fundamental damage detection capability of this sensor technology during fatigue testing of typical rotor blade materials. Therefore, a frequency modulated continuous wave (FMCW) radar sensor is used for damage diagnostics, and the results are validated by simultaneous camera recordings. Here, we focus on the failure modes delamination, fiber waviness (ondulation), and inter‐fiber failure. For each failure mode, three samples have been designed and experimentally investigated during fatigue testing. A damage index has been proposed based on residual, that is, differential, signals exploiting measurements from pristine structural conditions. This study shows that the proposed innovative radar approach is able to detect continuous structural degradation for all failure modes by means of gradual signal changes.